2003
DOI: 10.1002/chem.200390129
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous SmI2/H2O/Amine‐Mediated Reductions in THF

Abstract: The SmI(2)-mediated reductions of ketones, imines, and alpha,beta-unsaturated esters have been shown to be instantaneous in the presence of H(2)O and an amine in THF. The SmI(2)-mediated reductions are not only shown to be fast and quantitative by the addition of H(2)O and an amine, but the workup procedures are also simplified. Competing experiments with SmI(2)/H(2)O/amine confirmed that alpha,beta-unsaturated esters could be selectively reduced in the presence of ketones or imines. Comparison of analogue lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 34 publications
0
34
1
Order By: Relevance
“…The driving force for the reaction has been suggested to be the precipitation of the by-products. [14] When conjugated double and triple bonds were found to be rapidly reduced to simple alkenes or alkanes, it was concluded that the SmI 2 /H 2 O/amine mixture is a very powerful reductant (Scheme 17). [50] Scheme 17.…”
Section: Smi 2 /H 2 O/amine-mediated Reductionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The driving force for the reaction has been suggested to be the precipitation of the by-products. [14] When conjugated double and triple bonds were found to be rapidly reduced to simple alkenes or alkanes, it was concluded that the SmI 2 /H 2 O/amine mixture is a very powerful reductant (Scheme 17). [50] Scheme 17.…”
Section: Smi 2 /H 2 O/amine-mediated Reductionsmentioning
confidence: 99%
“…[14] The less sterically crowded 4-phenyl-2-butanone was reduced approximately 130 times faster than 2-methyl-3-heptanone with the reagent mixture SmI 2 /diglycol.…”
Section: Addition Of Alcohols and Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Divalent lanthanide complexes can function as oneelectron reductants, and especially samarium(II) complexes such as [SmI 2 (thf) 5 ] [1], [SmI 2 (hmpa) 4 ] [2], and [Sm(hmpa) 6 ]I 2 [3] have found extensive use as mild and selective reducing agents [4][5][6][7][8][9][10][11][12][13]. With the long-term goal of mastering the design and synthesis of enantioselective reducing agents, we have embarked on an exploratory synthesis project.…”
Section: Introductionmentioning
confidence: 99%
“…23 Careful tuning of reaction conditions revealed that freshly prepared samarium diiodide furnished lactonic ester 57 in the presence of triethylamine 24 as a ligand and acetic acid as a proton source in toluene as a single diastereomer. When the reaction was quenched by oxygen bubbling, recovery of the product was improved by minimizing side reactions with excess samarium diiodide.…”
Section: Synthesis Of Salvinorin a (1) : Second Generationmentioning
confidence: 99%